Provocando el desequilibrio de poder: Crítica a la política exterior de George W. Bush desde la Realpolitik - Diego Sazo Muñoz (Revista Enfoques, 2009)
The following article looks at George W. Bush's foreign policy critically, from a political realist point of view. The pivotal argument bases itself on the concept of balance of power. According to the author, since the fall of the Berlin Wall, the United States has had to confront a new global scenery, one which motivates the redesign of its foreign policies. Due to this change, political realism has lost its influence in the decision making process. In its replacement, neoconservatism has taken its place and since the beginning of Bush's administration, a new international orientation has been established: unilateral, hegemonic and ideological. This has provoked many conflicts and tensions with other international agents. The reason for the dilemmas, according to the author, rests in the failure of Bush's administration in applying balance of power.